2021
DOI: 10.1371/journal.pone.0245850
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis E virus antibodies in adults and children from upstate New York: A cross-sectional study

Abstract: Hepatitis E virus (HEV) is a major cause of viral hepatitis around the world, especially in developing countries. Recently, HEV has also been recognized as important cause of hepatitis in Europe and Japan, however, there is a paucity of clinical data from the United States. The overall seroprevalence of HEV antibodies is around 10% in the United States, but considerable variation is seen based on geographic location, year, and assay used. In this study, 63 adults and 417 children from New York State were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In our study, the global seroprevalence rate was shown to be eight to 10 times higher than rates reported in other studies in HICs (12,(22)(23)(24)(25)(26)(27). Interestingly, the age-related gradient reported non-hyperendemic areas was also observed in our study (12).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In our study, the global seroprevalence rate was shown to be eight to 10 times higher than rates reported in other studies in HICs (12,(22)(23)(24)(25)(26)(27). Interestingly, the age-related gradient reported non-hyperendemic areas was also observed in our study (12).…”
Section: Discussioncontrasting
confidence: 48%
“…Few studies have addressed the rates of HEV antibodies in children living in HICs (United States, Turkey, Spain, Portugal, and Russia); all of those reported rates were < 6% (22)(23)(24)(25)(26)(27). The unique study reporting high rates in children (34%) was performed in Southwestern France by the HEV Reference Laboratory using the same assay as used in our study.…”
Section: Discussionmentioning
confidence: 90%
“…A systematic review by Belei et al found that HEV seroprevalence estimates in individuals between 15 and 30 years can reach about 30% ( 63 ). Kmush et al studied HEV seroprevalence in both children and adults and found an overall seroprevalence of HEV antibodies among adults of 9.52% (95% CI: 3.58–19.59%) in contrast to a seroprevalence of 0.7% (95% CI: 0.15–2.09%) in children ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lower rates of IgG seropositive were observed during pregnancy in central Nigeria [14], Ethiopia [15] and South Africa [16]. Also much lower results among adults and children were found in France [17] and USA [18].…”
Section: Discussionmentioning
confidence: 92%